The Principle of Good Faith in Oral Pawn Agreements with Motor Vehicle Credit Collateral - Makruf Antoni, Amal Astana; Iskandar, Hardian (LEGAL BRIEF, 2025)
In general, when someone borrows from a bank or other financial institution, an agreement will usually be drawn up by both parties. However, most of these agreements are only made verbally without using a written agreement. This analysis aims to study the validity of credit agreements made through words or speech using property collateral in the form of motor vehicles, as well as the implementation of the principle of good faith in undocumented or unwritten credit agreements involving motor vehicle collateral. This analysis uses a normative-based legal approach and utilizes primary and secondary data sources obtained through literature studies, scientific articles, books, and provisions of legal articles related to the research topic. Information was collected using the minutes and documentation method and reviewed in depth. Observations show that the credit agreement through oral communication between Party 1 and Party 2 has fulfilled all the requirements under Article 1320 of the Civil Code. An agreement was made to borrow a certain amount of money with a motor vehicle as collateral. Party 1, in good faith, fulfilled all agreed provisions, including repayment of 30% of the loan with 8% monthly interest within three months